IMPLEMENTASI STRATEGI ACTIVE LEARNING DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDIT BAITUL JANNAH BANDAR LAMPUNG - Efendi, Rahmat; Masrur, Moh. (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2019)
The aim of this research is to describe active learning strategy to increase the students’ achievement at IV grade in Baitul Jannah SDIT and to describe the implementation of active learning strategy in islamic education lesson in Baitul Jannah SDIT. The kind of this research is quantitative research with data collective isusing observation, interview and documentation. And for data analyze is using qualitative descriptive, that is not in numbers but words form, sentence or paraghraph in descriptive form. Based on the result of the research can be concluded that aplly of active learning strategy in learning process of islamic education lesson in Baitul Jannah SDIT had been run well. When in teaching learning process thathad been done in the clas, such as students are active to ask the question that they have not understand yet, active to do the task  that had been given by the teacher. Between the methodes that had been used in islamic education lesson in Baitul Jannlah SDIT that direct to active learning strategy is asking and answering method, demonstration method, guided teaching, jigsaw learning, sane age tutor, memorize, role play, demonstration, quiz, and others. The implemtation of active learning strategy in teaching learning process of islamic education lesson in Baitul Jannah SDIT gives the good result for example their score in raport book, beside of their good score with active learning strategy the islamic education lesson that delivered in the class can apply in daily activities such as students love to read quran, pray 5 times, duhha sunnah pray, and other religious activites in islam.